2016
DOI: 10.1259/bjr.20150973
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasonography used for post-treatment responses evaluation of radiofrequency ablations for hepatocellular carcinoma: a meta-analysis

Abstract: Weixiang Shi and Ying He should both be regarded as first authors.Objective: This meta-analysis aims to analyze the usefulness of contrast-enhanced ultrasonography (CEUS) for posttreatment responses evaluation of radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC) management. Methods: Literature retrieval in three databases PubMed, Embase and Cochrane Library was conducted up to September 2015, with pre-defined criteria. The technical success rate, local tumour recurrence and local tumour progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…At one-month follow-up, contrast-enhanced CT represents the standard of care. High accuracy (91%) in the assessment of the residual tumor after ablative techniques was also demonstrated for CEUS in a meta-analysis [32].…”
Section: Discussionmentioning
confidence: 83%
“…At one-month follow-up, contrast-enhanced CT represents the standard of care. High accuracy (91%) in the assessment of the residual tumor after ablative techniques was also demonstrated for CEUS in a meta-analysis [32].…”
Section: Discussionmentioning
confidence: 83%
“…Contrast‐enhanced ultrasound is safe for patients with contraindications to computed tomography (CT) or magnetic resonance imaging (MRI), such as pacemakers, allergies to gadolinium‐based or iodinated contrast material, claustrophobia, immobility, or metal implants. Because of its lack of ionizing radiation and ease of performance without sedation, CEUS should be considered as a useful problem‐solving tool and as an indicated first‐line imaging modality in select settings as indicated below. Liver Characterization of focal liver lesions in the noncirrhotic liver. Further characterize incidentally found liver lesions on US examinations. Evaluate incompletely characterized lesions on noncontrast or contrast‐enhanced CT or MRI. Characterization of focal liver lesions in the cirrhotic liver. Assess nodules detected on surveillance US. Assess a Liver Imaging Reporting and Data System (LIRADS) category LR‐2, LR‐3, LR‐4, or LR‐M observation on prior contrast‐enhanced CT or MRI. Detect arterial‐phase hyperenhancement when mistiming is suspected as the reason for its absence on prior CT or MRI. Assess biopsied lesions with inconclusive histologic results. Detection of metastases. Vascular. Determine hepatic artery, portal vein, and hepatic vein patency. Assess transjugular intrahepatic portosystemic shunt patency. Distinguish a bland thrombus versus a tumor in a vein. Response to therapy (ablation or transarterial chemoembolization for hepatic malignancy) for assessment of residual viable disease Help select appropriate sites for biopsy. Assess for residual tumor after ablation. Kidney and bladder Antegrade nephrostogram for evaluation of ureteral patency in the setting of an indwelling nephrostomy tube …”
Section: Indicationsmentioning
confidence: 99%
“…A 2016 meta-analysis studied the results from 12 studies (772 patients with 933 lesions) on CEUS assessment of therapeutic response of RFA in HCC. The study reported 91% success rate of CEUS in evaluating the RFA response, which is comparable to CT-based methods [20]. A later meta-analysis reported that CEUS has sensitivity of 90% and specificity of 100% in A recent study examined the potential of MRI, CT, and ultrasound in predicting the response to antiangiogenic agent Sunitinib in patients with metastatic renal cell carcinoma (mRCC) [8].…”
Section: Ablation Response Assessmentmentioning
confidence: 99%